Electro-Facies and Petrophysical Properties of the Hartha Formation in Selected Wells of East Baghdad Oil Field - Abbas, Mohammed Sattam; Khudhair, Marwah Hatem; Al-Saadi, Osama Saad (Iraqi Journal of Science, 2022)
The Hartha Formation is a major carbonate succession deposited during the Late Campanian period. The current study depends on four selected wells (EB 1, 2, 4 and 30) within the East Baghdad oil field to study electrofacies and petrophysical properties related to the reservoir characterization. The Hartha Formation is divided into three electro-facies units using GR and SP logs in Petrel software. The upper unit of the Hartha Formation is composed mainly of limestone. The middle unit is composing of thick layers of shale. The lower unit is composed mainly of limestone with few shale layers. The three units are divided into three types of rocks in relation to the total porosity: 1. High-moderate active porosity rocks (type I). 2. Moderate active porosity rocks (type II). 3. Low-non pores rocks (type III). The lower unit represents the shale–dominated part of the Hartha Formation, with low to non-pores rocks (type III). This zone is revealed in all studied wells. These are limit presences for the high to moderate active porosity type (I) within the shale bands lithofacies appear in the studied wells. The middle unit is divided into two subzones. The upper part of this zone is characterized by high to moderate active porosity (type I), while the lower one shows moderate active porosity (type II) and low to non-pores rocks (type III) due to the high ratio content of shale. Upper rock-unit is expressed by high-moderate active porosity rocks (type I), which shale content is very low. This porosity type is identified through the upper unit at the East Baghdad oil field. These characteristic features are highly consistent with the low to moderate shale value rock unit.